Economic analysis of graphene aerogel polyurethane sponge production as adsorbent for oil-water separation. (2022) - Noer Addina, Septian; Idrus Alhamid, Muhammad; Usman, Anwar; Adi Prasetyanto, Eko; Sufyan, Muhammad; Kusrini, Eny
Abstract: In this study, economic feasibility of graphene aerogel polyurethane sponge (GAPU) production as an adsorbent for oil-water separation was investigated. GAPU has been made from graphite and it was further oxidized by the modified Hummers method to form graphene oxide (GO) or it was reduced to form reduced graphene oxide (rGO). The rGO was blended with polyurethane (PU) sponge and this rGO-PU composite was freeze-dried into an aerogel to change their shapes. This study was aimed to determine the economic parameters based on the scenarios of GAPU production being 547, 6, 000, and 12, 000 tons per year. The first scenario with a selling price of US 9.79/kg showed the net present value (NPV) of US 1, 241, 083.23, break event point (BEP) of 44.21%, internal rate of return (IRR) of 8.62%, and payback period (PBP) of 6.48 years. For the second scenario, the selling price is of US 2.62/Kg, NPV is US 10, 075, 984.08, BEP is 33.01%, IRR is 33.37%, and PBP is 2.21 years. The third scenario with an estimated selling price of US 2.05/Kg showed an NPV of US 17, 039, 863.70, BEP of 27.10%, IRR of 40.60%, and PBP of 2.19 years. The third scenario with GAPU production of 12, 000 tons is the best. Sensitivity analysis showed that the selling price of the product decreases by 10% is more unfavorable to the economic value than the price of raw materials increased by 10%. GAPU gets a cheaper selling price than other methods with provided that the economic value is fullfilled when NPV is positive, BEP is less than 50%, and IRR is higher than 15%, and the removed oil can be reused and potential for sale. Finally, it can be concluded that the production of GAPU is feasible.